Mental Health of University Students in Northern Malaysia - Maung Maung, Theingi; Win, Phyo Thet Naing; Oo, Win (National Journal of Community Medicine, 2023)
Context/Background: Today, poor mental health is one of the most neglected diseases although it is one of the leading causes of disabilities in both developed and developing countries. This mental health issue becomes a problem among university students too. This study was aimed to determine the prevalence and associated factors of depression, anxiety, and stress (DAS) among university students. Methodology: A cross-sectional study was carried out in a private university of northern Malaysia during 2020. A random sample of 161 students were included and DASS-21 was used to determine the prevalence of DAS. Multiple logistic regression analysis was performed to examine the associated factors. Results: The prevalence of DAS among students were 34.8%, 42.2%, and 33.5%, respectively. In contrast to years 2 and 4, the prevalence of all types of mental disorders were lower in years 1 and 3. The students’ living area, residence, academic year, and parental income were significantly associated with anxiety whereas the age group of the students and parent’s income did so for depression. The variables; age group, academic year and parent’s income were identified as significant determinants for the presence of stress among students. Conclusions: The significant extent of the mental health problems was detected among university students in Malaysia. Despite the small sample, this analysis indicates that opportunities exist to improve campus-based mental health education and psychological support among university students.